К вопросу таможенного тарифа и его основных элементов - Жуковская, О. А. (БНТУ, 2020)
The scientific article deals with the topic of the customs tariff and its main elements, as well as the specifics of the impact of the customs tariff on the development of foreign trade relations and the economy. Such issues as the concept, basis, principles, elements and types of customs tariff are considered